Long-term visual and systemic prognoses of 83 cases of biopsy-proven sarcoid uveitis. Issue 7 (25th November 2016) - Rochepeau, Cédric; Jamilloux, Yvan; Kerever, Sebastien; Febvay, Camille; Perard, Laurent; Broussolle, Christiane; Burillon, Carole; Kodjikian, Laurent; Seve, Pascal
Abstract : Aims: To determine the long-term visual and systemic outcomes of uveitis patients with biopsy-proven sarcoidosis. Methods: A retrospective study of biopsy-proven sarcoid uveitis, with a 3-year minimum follow-up, seen at Lyon University Hospital, between April 2004 and January 2016. Results: A total of 83 patients were included, with a median age at onset of 52 (37−62) years and an unbalanced gender ratio (women 77.1%). Thirty-one patients had original systemic sarcoidosis in addition to ocular localisation, whereas 52 initially presented with isolated sarcoid uveitis. Among the latter, 7.7% (n=4) developed an extraocular disease after a median follow-up duration of 60 (44−110) months. The systemic spread in these patients included cutaneous sarcoids (n=2), arthritis (n=1) and multiple mononeuritis (n=1). Complete visual recovery was obtained for 60.2% of all patients and 89.2% had retrieved best-corrected visual acuity (BCVA) >20/50 in both eyes. A unilateral loss of BCVA of worse than 20/200 was documented in two patients in the isolated sarcoid uveitis group. No patient suffered from bilateral severe visual impairment or blindness. Factors linked to a poor visual prognosis, defined by BCVA ≤20/50 in at least one eye, were chronic macular oedema (p=0.009) and persistent ocular inflammation (p=0.0005). Conclusions: In this large European series of biopsy-proven sarcoidosis to date, with a prolonged follow-up, sarcoid uveitis was suggestive of a favourable systemic and visual outcome. Clinically isolated uveitis that revealed sarcoidosis remained a strictly ocular condition in most cases.